Common Bottlenose Dolphin Protection and Sustainable Boating: Species Distribution Modeling for Effective Coastal Planning - La Manna, Gabriella; Ronchetti, Fabio; Sarà, Gianluca; Ruiu, Alberto; Ceccherelli, Giulia (Frontiers in Marine Science, 2020)
Indicators for preserving marine biodiversity include knowledge of how the spatial distribution and critical habitats of species overlap with human activities and impacts. Such indicators are key tools for marine spatial planning, a process that identifies and resolves conflicts between human uses and the conservation of marine environments. The common bottlenose dolphin in the Mediterranean Sea is considered a vulnerable species by the IUCN Red List and a priority species of the EU Habitat Directive. Here, we estimated spatio-temporal patterns of the species occurrence in the area around one Marine Protected Area (MPA) and two Sites of Community Importance (SCI) of the North western Sardinia, with the aim to predict the species distribution and the main links with the environmental factors and boat traffic. To evaluate whether dolphin groups with calves showed any habitat preference different from groups without calves, separate models for both type of groups were done. The most important contributing variables to the dolphin habitat suitability models were the likelihood of boat presence, habitat type and mean sea surface temperature. Different model outputs were obtained depending on dolphin group composition. The area of high likelihood of dolphin presence ranged between 30 and 60 km2 and was smaller for groups with calves. Further, the area of highest dolphin habitat suitability overlaps with the area of high boat traffic, suggesting that boating in the study site is a potential relevant anthropogenic threat to dolphins. Particularly, boating is concentrated inside and around the MPA/SCIs, indicating the need for stronger restriction measures. We propose updated SCI boundaries for effective protection of common bottlenose dolphins. These areas and the suggestions of regulation are specifically aimed at reducing the impact of boating on dolphins, especially for groups with calves. Synthesis and applications. Management measures should be designed based on the data here provided, and then implemented and enforced to decrease dolphin-boat interactions, especially for mother-calf pairs. The creation of new coastal SCIs should be considered especially where boat traffic overlaps with areas most suitable for dolphins. In these SCIs, boating should be managed to limit disturbance, avoidance or alterations of dolphin vital behaviour.